2001
DOI: 10.1038/35092584
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p16Ink4a confers susceptibility to metastatic melanoma in mice

Abstract: CDKN2A (INK4a/ARF) is frequently disrupted in various types of human cancer, and germline mutations of this locus can confer susceptibility to melanoma and other tumours. However, because CDKN2A encodes two distinct cell cycle inhibitory proteins, p16INK4a and p14ARF (p19Arf in mice), the mechanism of tumour suppression by CDKN2A has remained controversial. Genetic disruption of Cdkn2a(p19Arf) (hereafter Arf) alone predisposes mice to tumorigenesis, demonstrating that Arf is a tumour-suppressor gene in mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
392
1
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(417 citation statements)
references
References 25 publications
(26 reference statements)
20
392
1
4
Order By: Relevance
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…In the HPV-negative tumors both p14 ARF as well as p16 INK4A were often undetectable, which is in accordance with the fact that their expression is downregulated in most headand-neck squamous cell carcinomas due to gene inactivation at the 9p21 locus. 45,46 In normal tissue cells, p14 ARF upregulation might lead to p53 upregulation, but in HPV-positive tonsillar squamous cell carcinomas, this is usually counteracted by means of functional inactivation of wild-type p53 by the viral E6 protein. In contrast and as observed in our study, p53 is frequently upregulated in HPVnegative tumors due to mutations in the TP53 gene as a result of exposure to tobacco and/or alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 flox/flox (Marino et al, 2000) and p16 ink4aÀ/À (Krimpenfort et al, 2001) mice were kindly provided by A Berns. All mice used for this analysis were predominantly on a FVB/N mixed strain, with Figure 7 Proposed model of meningioma initiation in the mesoderm-and neural crest-derived meningeal lineages.…”
Section: Micementioning
confidence: 99%
“…9 In fact, many of the melanoma-associated tumor suppressor genes identified to date are themselves involved in control of senescence, including BRAF (encoding serine/threonine-protein kinase B-raf), CKD4 (cyclin-dependent kinase 4), and CDKN2A (encoding cyclin-dependent kinase inhibitor 2A isoforms p16 INK4a and p19 ARF ). 3,10 Nevi frequently harbor oncogenic mutations of the tyrosine kinase BRAF gene, particularly V600E, 11 and BRAF V600E is also found in approximately 70% of cutaneous melanomas. 12 Expression of BRAF V600E in human melanocytes leads to oncogene-induced senescence, 8 which can be considered as a mechanism that protects from malignant progression.…”
mentioning
confidence: 99%